Günəş-hidrogen hibrid enerji texnologiyalarının təkmilləşdirilməsi - Səfərov, Şəmsəddin; Səfərov, Rantik (My University, 2024)
The aim of the dissertation is to develop a solar-hydrogen hybrid power supply system for remote residential areas. In rural areas, forests are increasingly diminishing, environmental pollution is rising, and the energy demand is growing. In this context, using sustainable, clean, and environmentally friendly energy sources is of great importance. To achieve this goal, an energy supply system based on the combined use of solar and hydrogen energy has been investigated. The research work explores renewable energy sources, focusing on the generation of electricity from solar energy and the production of hydrogen from that energy. Various methods for obtaining hydrogen from solar energy have been examined.
Improvement of solar-hydrogen hybrid energy technologies
Keywords: Renewable energy; Hydrogen production